Pengaruh Sarana Prasarana Sekolah terhadap Hasil Belajar Siwa pada Teknik Dasar Menjahit Kelas X SMK Dharma Wanita Gresik - Adela Rosa Nadia Fransiska; Imami Arum Tri Rahayu; Peppy Mayasari; Mein Kharnolis (Departement of Mathematics Education, 2024)
Infrastructure is a base facility to support the implementation of learning. The objectives of the study were 1) describe the feasibility of the sewing practice laboratory at Smk Dharma Wanita Gresik, 2) describe student learning outcomes on basic sewing techniques at Smk Dharma Wanita Gresik, 3) describe the influence of infrastructure on student learning outcomes on basic sewing techniques at Smk Dharma Wanita Gresik. Using a quantitative approach, the research was carried out in class X fashion with a total of 12 students. Data collection techniques using questionnaires and performance tests. Data analysis techniques use simple regression analysis. The results of the study 1) school infrastructure facilities on the Linkert scale have an interval value of 50% in the category of not feasible 2) student learning outcomes on basic sewing techniques are shown with a percentage of 41.7% incomplete and 58.3% complete 3) t-count calculations of 5,186 > 2,179 t-tables with a significance level of 0.05. School infrastructure has a significant influence on the learning outcomes of basic sewing techniques in class X of SMK Dharma Wanita Gresik.